THE USE OF MUSIC IN THE SEARCH FOR HUMANIZED HOSPITAL CARE - Corrêa, Ione; Guedelha Blasi, Debora (Investigación y Educación en Enfermería, 2009)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Objective: Our objective was to identify advantages and disadvantages for the nursing team in using music when looking for humanized care. Methodology: This was a qualitative study, where subjects are nurses, technicians, and nursing assistants in the Paediatric inpatient isolation unit HC-UNESP. The team answered questions relating to their perceptions of advantages and disadvantages in using music with hospitalized children. Results: the interviewed people perceive music as something beneficial and think that that type of performance would have to occur more times to provide to the boy and the own equipment effects like relaxation, tranquillity, greater facility of interaction between the boy and the equipment. Conclusion: this study suggests there is a need to promote the potential of music in healthcare and stimulate the whole team to reflect on using music as a humanizing strategy,and even as an alternative treatment, for those staying in hospital, and using this resource when seeking to provide humanized care.